Measuring Hard-to-Measure Student Competencies A Research and Development Plan - Stecher, Brian M. (RAND Corporation, 2014)
Interpersonal and intrapersonal competencies, such as communication and resilience, are important predictors of success and civic engagement after high school. This report provides guidelines to promote thoughtful development of practical, high-quality measures of interpersonal and intrapersonal competencies that practitioners and policymakers can use to improve valued outcomes for students.